The nutritional status and nutrition habits in a group of patients with end stage renal failure treated with hemodialysis - Moszak, Małgorzata; Kucharski, Marcin Andrzej; Kondracka, Ewelina; Grzymisławski, Marain (Journal of Medical Science, 2017)
Aim. The aim of the study was to assess the nutritional status and nutrition habits in a group of patients with end stage renal failure treated with hemodialysis.Material and Methods. The study group consisted of 50 patients treated with hemodialysis, including 16 women and 34 men. The average age of researched patients was 67.02 ± 10.71 years. We used an authorial questionnaire in the research, which contained questions about feeding behavior and nutritional status. In addition, patients underwent anthropometric measurements.Results. The research revealed that the nutritional status of patients with chronic kidney disease treated with hemodialysis was poor. The supply of energy, carbohydrates, protein and dietary fiber in the studied group were 1583.41 ± 379.55 kcal, 222.68 ± 55.08 g, 63.75 ± 15.25 g and 55.75 ± 18.55 g respectively, which were all below the standard daily requirement. The deficiencies of magnesium, iron and vitamins were also observed. More than half of respondents (52%) ate only 3 meals a day.Conclusions. The results of research show that both – nutritional state and eating habits of patients were abnormal and deviated from the dietary recommendations for this group of patients. Changes of the nutrition will positively influence the nutritional state of patients, as well as improve their quality and length of life.